Microbial Biomass Carbon, Nitrogen and Phosphorus in Soils of Natural Forests in India: The impact of trimming frameworks on soil physicochemical properties and microbial biomass in natural forests of India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In this examination, the effect of trimming frameworks on physicochemical properties of soil and microbial biomass was assessed. Soil was gathered from four developed fields (cropland, crop + single tree species, crop + different tree species and homegardens) and one crude (horticulturally disposed of) field and broke down. The result of the current investigation demonstrated that developed land wasted about 14 C and 5 N in 8 years of development to the close by crude land. Soil microbial biomass of developed land with different tree species (C + mT) was more noteworthy than different frameworks and showed a considerable occasional variety. The microbial biomass carbon (Cmic) grouped from 166 to 266 μg g–1 and microbial biomass nitrogen (Nmic) from 11 to 41 μg g–1. Cmic contributed 1.25–1.90 of soil C and Nmic 0.83–3.77 of soil N. Among developed land, greatest Cmic and Nmic were accounted for in C + mT framework which recommended that tree estate in developed land has critical constructive outcomes on microbial biomass and other soil properties by moving natural soil properties under the comparative ecological conditions.